The Myths of ’Broken’ Government: Moving Beyond the Conventional Wisdom - Cahill, Anthony (Maine Policy Review, 1993)
The budget difficulties faced by Maine and by most other states have prompted a national search for better ways to deliver government services. In Maine, a conference entitled "Rethinking Maine Government" was held at the University of Maine on January 5-6, 1993 under the auspices of the Margaret Chase Smith Center for Public Policy. Maine Policy Review selected three of the presentations at that conference for this issue. Anthony Cahill challenged the 400 legislators, state government officials and business leaders attending the conference to think in terms of a "revolution" in rethinking Maine’s state government.